Prevalence and risk factors of irritable bowel syndrome in adolescents - Muzal Kadim; Aida Rosita Tantri; Muhammad Indera Ramadani (Indonesian Pediatric Society, 2021)
Background Irritable bowel syndrome (IBS) is a common gastrointestinal disorder in children and adults. The IBS is diagnosed by symptoms that fulfill the Rome IV criteria. This condition can impact quality of life, especially in adolescents. Objectives To investigate the prevalence of IBS in high school students and analyze its risk factors. Methods This cross-sectional study was done with e-questionnaires from Rome IV Diagnostic Questionnaire on Pediatric Functional Gastrointestinal Disorders (R4PDQ). Students from high school and occupational schools age 14 to 18-years-old in Jakarta were included in this study. Possible risk factors for IBS were analyzed using Fisher’s exact test for bivariate analysis and logistic regression for multivariate analysis. Results Of 210 subjects, 10 (4.8%) had IBS. The IBS-M and IBS-C subtypes were more common than IBS-D. Gastrointestinal infection history was significantly associated with IBS (OR 7.1; 95%CI 1.7 to 29.3; P=0.013). Other factors such as gender, corporal punishment, asthma, spicy and fatty food consumption, as well as socioeconomic status were not significantly associated with IBS (P>0.05). Conclusion The prevalence of IBS in adolescents is 4.8%. History of gastrointestinal infection is a risk factor for IBS.